1998
DOI: 10.1046/j.1471-4159.1998.70062357.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 and 4‐Aminopyridine Prevent the Lipopolysaccharide‐Induced Outwardly Rectifying Potassium Current and Interleukin‐1β Production in Cultured Rat Microglia

Abstract: Abstract:Brain inflammation includes microglial activation and enhanced production of diffusible chemical mediators, including prostaglandin E,. Prostaglandin E, is generally considered a proinflammatory molecule, but it also promotes neuronal survival and down-regulates some aspects of microglial activation. It remains unknown, however, if and how prostaglandin EP prevents microglial activation. In primary culture, microglial activation is predicted by a characteristic pattern of whole-cell potassium currents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 58 publications
1
37
0
Order By: Relevance
“…In addition to 15d-PGJ 2 , anti-inflammatory roles of PGE 2 have been suggested. PGE 2 reduces the expression of inducible NO synthase (iNOS) and IL-1␤ (35,36). PGE 2 increases levels of anti-inflammatory lipid mediators, such as lipoxins (30,37).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to 15d-PGJ 2 , anti-inflammatory roles of PGE 2 have been suggested. PGE 2 reduces the expression of inducible NO synthase (iNOS) and IL-1␤ (35,36). PGE 2 increases levels of anti-inflammatory lipid mediators, such as lipoxins (30,37).…”
Section: Discussionmentioning
confidence: 99%
“…All these observations can be summarized by saying that PGE 2 concentrations between 1 and 10 M inhibit I K by 50% or less. Much greater PGE 2 sensitivity has been reported for the lipopolysaccharide-induced K + outward current in cultured rat microglia: 50% inhibition by 10 nM, 80% inhibition by 100 nM PGE 2 [17]. PGE 2 (100 nM) almost totally blocks the Ca 2+ -activated K + current which gives rise to a slow, Ca 2+ -dependent spike after-hyperpolarization in rabbit nodose neurons [118].…”
Section: Potassium Channelsmentioning
confidence: 86%
“…Also, the enhancement of the capsaicin-induced inward current by PGE 2 (see Fig. 4A) is mimicked by forskolin and completely blocked by intracellular perfusion of the PKA inhibitor PKI [14][15][16][17][18][19][20][21][22][23][24] [64]. Sensitization of mechanosensitive channels by PGE 2 is blocked by the PKA inhibitor H-89, an isoquinoline sulfonamide [20].…”
Section: C) Mechanism Of Action Ep Receptors Acting Via Camp-dependenmentioning
confidence: 99%
“…It was shown that PGE2-PTGER4 signaling in mammalian macrophages suppressed the stimulus-induced expression of certain proinflammatory genes, including tumor necrosis factor (TNF)-a, interferon (IFN)-b and macrophage inflammatory protein (MIP)-1b [14,17]. Reportedly, in the setting of LPS stimulation, PGE2 signaling via PTGER4 decreased the levels of interleukin-1beta (IL-1b) [18] and inducible nitric oxide synthase (iNOS) [19] in microglia. Additionally, overexpression of PTGER4, as well as PTGER2, resulted in a significant reduction in the LPS-induced mRNA expression of proinflammatory chemokine monocyte chemotactic protein-1 (MCP-1) in glomerulonephritis [20].…”
Section: Introductionmentioning
confidence: 99%